ON THE INFLUENCE OF THE WEAR RESISTANCE OF GRATE BARS ON THE TECHNOLOGICAL GAP BETWEEN THEM IN FIBER SEPARATING MACHINES - A, Yusupov; R, Muminov; K, Iskandarova; G, Shin (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents materials on a comparative analysis of the influence of the wear resistance of cast iron grates on the technological gap between them, taking into account preliminary dynamic treatment with microballs and without treatment. An equation for the development of wear on gin grates was obtained based on data from experimental studies of their wear under operating conditions.